Depression and anxiety in female refugees from East Africa and the Middle East displaced to Germany: cross-sectional results of the female refugee study, taking sociodemographic and migration-related factors into account - Bohland, Helena Katharina; Kimbel, Renate; Kegel, Peter; Dietz, Pavel; Koestner, Clemens; Letzel, Stephan; Kurmeyer, Christine; Jesuthasan, Jenny; Schouler-Ocak, Meryam; Zier, Ulrike (Frontiers in Psychiatry, 2024)
At the end of 2022, 108.4 million people around the world were forcibly displaced, the highest number ever recorded. Of these, 50% were women. Despite this situation, little is known about the mental health of female refugees. The first aim of this study was to examine the prevalence of depression and anxiety symptoms among female refugees in Mainz, Germany. The second aim was to examine which sociodemographic and migration-related variables have an impact on refugees' mental health, and the third aim was to assess the potential predictors of their mental health.A sample of 92 female refugees from East Africa and the Middle East living in Mainz Germany were interviewed. Symptoms of depression and anxiety were assessed using the Hopkins Symptom Checklist (HSCL-25). The experience of potentially traumatic events (PTEs) was assessed using the Posttraumatic Diagnostic Scale (PDS) and the Harvard Trauma Questionnaire (HTQ).In our sample of female refugees, 65.2% reported symptoms of depression, and 60.9% reported symptoms of anxiety. Symptoms of depression or anxiety were associated with being from the Middle East, having a higher level of education, and reporting more PTEs. The multiple regression model for anxiety was able to explain 32.4% of the variance in anxiety symptoms.The findings highlight the high burden of mental health problems that female refugees bear. The identified predictors of depressive and anxiety symptoms should sensitize medical and refugee professionals to identify vulnerable individuals and groups, refer them to appropriate psychological treatment, and, where possible, modify the identified predictors.